An?lise de Desempenho Experimental de Redes LTEAdvanced Baseadas em MIMO e Agrega??o de Portadoras - Rodovalho, T?rsio Naves (2017)
The main goal of this work is presenting an experimental performance analysis of the physical layer (PHY) of the fourth generation (4G) LTEAdvanced mobile networks based on carrier aggregation (CA) and MIMO. The CA technique allows the combination of bandwidth fractions from different spectral bands, with the purpose of increasing the signal bandwidth and, consequently, maximizing the system throughput. The implementation has been based on the use of three 20MHz component carriers (CCs), in the 2600MHz, 1800MHz and 700MHz frequency bands, and a 2?2 MIMO antenna configuration. Furthermore, two Category 16 (256QAM) and Category 9 (64QAM) mobile devices with nominal rates of 600 and 450Mbps, respectively, have been employed. Comparing the theoretical rates proposed by the 3GPP specifications with the experimental data obtained in this work will enable to comprehend the applicability and efficiency of the two applied. The LTE-A network implementation has been divided into five phases: description of the LTE and LTE-A network architectures; the use of MIMO antenna arrangements to increase the spectral efficiency; the main properties of the multi-carrier aggregation used in LTE-A; theoretical analysis of LTE-A networks; implementation and configuration of different scenarios of LTE-A networks, as well experimental performance investigations as a function of throughput, BLER, CQI and RSRP. Experimental results demonstrate 600Mbps wireless transmission using 3CCs and 2?2 MIMO.